Crowdsourcing Local Attacks: ISIS Expands its Radical Reach - Syed Huzaifah Othman Alkaff (2017)
The Islamic State of Iraq and Syria (ISIS) has taken to crowdsourcing local attacks to make up for its losses in the Middle East. This has become a major plank of the group’s strategy to expand its radical reach and inflict global violence.